2019
DOI: 10.1002/gch2.201800108
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrical Conductivity of Sb2S3 Thin Film via C60 Modification and Improvement in Solar Cell Efficiency

Abstract: Sb 2 S 3 has attracted great research interest very recently as a promising absorber material for photoelectric and photovoltaic devices because of its unique optical and electrical properties and single, stable phase. However, the intrinsic high resistivity property of Sb 2 S 3 material is one of the major factors restricting the further improvement of its application. In this work, the C 60 modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The middle sub-band centered at −10.7 eV (g-Sb 2 S 3 ) or −10.0 eV (L-Sb 2 S 3 ) has predominantly the s-character as well as the low-energy part at approximately −15 eV. The bandgap for glassy ( E g = 2.28 eV) and liquid ( E g = 1.06 eV) antimony sesquisulfide are consistent with the reported optical data 1,76–79 and electrical measurements (Fig. 2).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The middle sub-band centered at −10.7 eV (g-Sb 2 S 3 ) or −10.0 eV (L-Sb 2 S 3 ) has predominantly the s-character as well as the low-energy part at approximately −15 eV. The bandgap for glassy ( E g = 2.28 eV) and liquid ( E g = 1.06 eV) antimony sesquisulfide are consistent with the reported optical data 1,76–79 and electrical measurements (Fig. 2).…”
Section: Resultssupporting
confidence: 87%
“…75 The obtained results are consistent with the reported values of conductivity parameters and optical bandgap E g for bulk crystalline samples and amorphous or crystalline thin films, 1.5 r E g (c-Sb 2 S 3 ) r 1.8 eV and 2.0 r E g (a-Sb 2 S 3 ) r 2.4 eV. 1,[76][77][78][79] In addition, the conductivity seems to be intrinsic since 2E a D E g .…”
Section: Glass-forming Thermal and Electric Propertiessupporting
confidence: 84%
“…Therefore, compared with pristine-Sb 2 S 3 and other alkali metal-doped Sb 2 S 3 -based absorber solar cells, Cs-doped Sb 2 S 3 -based absorber solar cell attained the top efficiency of 6.56% (Figure 5d). Guo et al [61] modified the absorber Sb 2 S 3 with C 60 . XRD and transmittance spectra confirmed that modified films did not make any lattice distortions, but resulted in enhanced electrical conductivity and device performance.…”
Section: Doping Effects On Sb 2 S 3 Solar Cell Performancementioning
confidence: 99%
“…The peaks at ∼280 and 303 cm −1 can be assigned to the anti-symmetric Sb–S and symmetric stretching modes of Sb–S bonds, respectively. 35–39 Compared to the p-Sb 2 S 3 sample, a higher Raman peak intensity is noted at 303 cm −1 for Sb 2 S 3 –H 2 /Ar, an indication of enhanced symmetric Sb–S stretching due to reduced defect density. The Raman measurement of a single Sb 2 S 3 –H 2 /Ar rod at different positions was also performed (Fig.…”
Section: Resultsmentioning
confidence: 94%